Policy Spillover and Gun Migration: The Interstate Dynamics of State Gun Control Policies*. (June 2017) - Coates, Michael; Pearson‐Merkowitzz, Shanna
Abstract : Objective: In this article, we examine state policy spillover by examining how differences between state gun control policies affect the migration of guns between states with lax regulatory environments for gun purchasing and licensing to states with relatively strict regulatory environments. Method: We test our hypothesis using data from 2007 to 2013 from the Bureau of Alcohol, Tobacco and Firearms on the presence of criminal guns and from the Brady Campaign on state gun control laws. Results: Our results suggest that a large proportion of criminal guns in states with strict gun control laws were originally purchased in states with fewer regulations. There is a direct correlation between where criminal guns were originally purchased, where criminal guns are uncovered, and the strength of state gun laws. Conclusion: State gun control laws appear to make purchasing a gun through legal frameworks more difficult and shift the "market" for criminal guns to purchasing locations across state borders where purchasing is easier. Gun control laws appear, therefore, to be affected by policy spillover.